β2 integrin regulates neutrophil trans endothelial migration following traumatic brain injury - Lei Li; Ruilong Peng; Cong Wang; Xin Chen; Dilmurat Gheyret; Siyu Guan; Bo Chen; Yafan Liu; Xilei Liu; Yiyao Cao; Cha Han; Jianhua Xiong; et al. (Cell Communication and Signaling)
Abstract Neutrophils are the first responders among peripheral immune cells to infiltrate the central nervous system following a traumatic brain injury (TBI), triggering neuroinflammation that can exacerbate secondary tissue damage. The precise molecular controls that dictate the inflammatory behavior of neutrophils post-TBI, however, remain largely elusive. Our comprehensive analysis of the molecular landscape surrounding the trauma in TBI mice has revealed a significant alteration in the abundance of β2 integrin (ITGB2), predominantly expressed by neutrophils and closely associated with immune responses. Using the fluid percussion injury (FPI) mouse model, we investigated the therapeutic efficacy of Rovelizumab, an agent that blocks ITGB2. The treatment has demonstrated significant improvements in neurologic function in TBI mice, attenuating blood–brain barrier permeability, mitigating oxidative stress and inflammatory mediator release, and enhancing cerebral perfusion. Moreover, ITGB2 blockade has effectively limited the adherence, migration, and infiltration of neutrophils, and has impeded the formation of neutrophil extracellular traps (NETs) upon their activation. Finally, it was demonstrated that ITGB2 mediates these effects mainly through its interaction with intercellular adhesion molecule-1 (ICAM 1) of endotheliocyte. These findings collectively illuminate ITGB2 as a crucial molecular switch that governs the adverse effects of neutrophils post-TBI and could be targeted to improve clinical outcome in patients.